2011
DOI: 10.3109/09553002.2010.537429
|View full text |Cite
|
Sign up to set email alerts
|

Ionising radiation triggers fat accumulation in white adipose tissue

Abstract: A physical agent such as γ-rays can trigger biological responses resulting in fat accumulation of gonadal white adipose tissue in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 21 publications
(23 reference statements)
3
12
1
Order By: Relevance
“…We also observed a large increase in the levels of TGs and ChoE, which has been reported in previous studies with 6 Gy of external irradiation in rats 20 and 5 Gy of whole-body external irradiation in mice 21 . Although the levels of these lipids reverted back to normal after one radiation exposure, in our current study the 90 Sr exposure-induced increases persisted until the end of the experiment, day 30 at 5.2±0.73 Gy.…”
Section: Resultssupporting
confidence: 90%
“…We also observed a large increase in the levels of TGs and ChoE, which has been reported in previous studies with 6 Gy of external irradiation in rats 20 and 5 Gy of whole-body external irradiation in mice 21 . Although the levels of these lipids reverted back to normal after one radiation exposure, in our current study the 90 Sr exposure-induced increases persisted until the end of the experiment, day 30 at 5.2±0.73 Gy.…”
Section: Resultssupporting
confidence: 90%
“…Although many in vitro and short-term in vivo studies have shown that IR can induce premature senescence [20,23,36], long-term in vivo studies are lacking. We previously reported that IR can produce long-term alterations of immunological functions and lipid metabolism, and the fractionation scheme can modulate the effects of IR [14,25]. Therefore, the present study was performed to examine the long-term effects of IR on tissue senescence in mice up to 6 months following IR exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the effect of irradiation delivery, such as single or fractionated doses, on senescence marker expression was evaluated. We previously reported that more prominent prolonged effects on immunological functions and lipid metabolism are observed when irradiation is given in fractionated doses than in a single dose [14,25]. For our investigation, mice were given single or fractionated doses of IR (in a total dose of 5 Gy), and senescence marker expression in the mouse tissues was analyzed 2, 4, and 6 months after irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…In adipose tissue of the irradiated rats, incorporation of 14 C-glucose into all the lipid fractions was raised throughout the time of observation (300–600% of the control value). Jo et al (17) exposed two-month-old C57BL/6 mice to whole-body radiation at a single dose (5 gray [Gy]) and found that the mRNA levels of glucose transporter 4 (GLUT4) in gonadal white fat was lower in the gamma-irradiated groups vs. un-irradiated animals.…”
Section: Discussionmentioning
confidence: 99%